2016
DOI: 10.1007/s10803-016-2700-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring What’s Missing: What Do Target Absent Trials Reveal About Autism Search Superiority?

Abstract: We used eye-tracking to investigate the roles of enhanced discrimination and peripheral selection in superior visual search in autism spectrum disorder (ASD). Children with ASD were faster at visual search than their typically developing peers. However, group differences in performance and eye-movements did not vary with the level of difficulty of discrimination or selection. Rather, consistent with prior ASD research, group differences were mainly the effect of faster performance on target-absent trials. Eye-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…One study used the Autism Spectrum Quotient to screen participants, with a cut‐off of < 25 for the control group to ensure that undiagnosed or subclinical ASD would not affect the results. Overall there was some diversity in the manner in which individuals with ASD were confirmed with some studies relying on a prior diagnosis made by either a clinical psychologist 3,46 or psychiatrist or simply ‘clinicians’ . However, for the majority at least one of the study authors confirmed the diagnosis within the study centre using the Autism Diagnostic Observational Schedule, Diagnostic and Statistical Manual IV or Autism Diagnostic Interview‐Revised …”
Section: Methodsmentioning
confidence: 91%
See 3 more Smart Citations
“…One study used the Autism Spectrum Quotient to screen participants, with a cut‐off of < 25 for the control group to ensure that undiagnosed or subclinical ASD would not affect the results. Overall there was some diversity in the manner in which individuals with ASD were confirmed with some studies relying on a prior diagnosis made by either a clinical psychologist 3,46 or psychiatrist or simply ‘clinicians’ . However, for the majority at least one of the study authors confirmed the diagnosis within the study centre using the Autism Diagnostic Observational Schedule, Diagnostic and Statistical Manual IV or Autism Diagnostic Interview‐Revised …”
Section: Methodsmentioning
confidence: 91%
“…Therefore, all participants in the ASD groups received confirmation of the diagnosis of ASD, hence minimising the potential for selection bias within this population. Conversely, only four studies included a screening for ASD traits within the typically developed comparison group, creating a potential for selection bias in the other 11 studies, as participants in the comparison group may have exhibited some ASD traits. These studies were therefore graded as having moderate risk of selection bias.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One particular strength, performance on visual search tasks (VSTs), which require participants to locate a target item embedded within an array of distractors, has been shown in infants at elevated risk for ASD [i.e., infants with an older sibling with ASD; Gliga et al, 2015], as well as toddlers, school-aged children, adolescents, and adults diagnosed with ASD [Kaldy, Giserman, Carter, & Blaser, 2016]. Furthermore, faster, more efficient search abilities are associated with higher levels of ASD symptomatology [Gliga et al, 2015;Joseph, Keehn, Connolly, Wolfe, & Horowitz, 2009;Keehn & Joseph, 2016;Keehn, Shih, Brenner, Townsend, & Müller, 2013], suggesting that nonsocial attentional processes, and the differences in brain function that these behaviors reflect, may be of etiological significance in the development of ASD.…”
Section: Introductionmentioning
confidence: 99%